2012
DOI: 10.1242/dmm.008730
|View full text |Cite
|
Sign up to set email alerts
|

Liver hyperplasia after tamoxifen induction of Myc in a transgenic medaka model

Abstract: SUMMARYMyc is a global transcriptional regulator and one of the most frequently overexpressed oncoproteins in human tumors. It is well established that activation of Myc leads to enhanced cell proliferation but can also lead to increased apoptosis. The use of animal models expressing deregulated levels of Myc has helped to both elucidate its function in normal cells and give insight into how Myc initiates and maintains tumorigenesis. Analyses of the medaka (Oryzias latipes) genome uncovered the unexpected pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…It could also provide a sensitized background in which a single additional deregulated oncogene can trigger tumorigenesis, thus enabling new oncogenes to be uncovered and studied in the economical and potentially high-throughput zebrafish model. Recently, myc transgenic medaka with liver hyperplasia have also been reported (Menescal et al, 2012) and consistent observations were produced from the two complementing transgenic fish models. It is also interesting to note that Myc-induced mouse HCCs could be rapidly regressed after inactivation of Myc expression (Felsher, 2010; Jain et al, 2002; Shachaf et al, 2004).…”
Section: Discussionmentioning
confidence: 60%
“…It could also provide a sensitized background in which a single additional deregulated oncogene can trigger tumorigenesis, thus enabling new oncogenes to be uncovered and studied in the economical and potentially high-throughput zebrafish model. Recently, myc transgenic medaka with liver hyperplasia have also been reported (Menescal et al, 2012) and consistent observations were produced from the two complementing transgenic fish models. It is also interesting to note that Myc-induced mouse HCCs could be rapidly regressed after inactivation of Myc expression (Felsher, 2010; Jain et al, 2002; Shachaf et al, 2004).…”
Section: Discussionmentioning
confidence: 60%
“…Temporary up-regulation of Myc is known to occur during hepatic regeneration while sustained up-regulation is linked to neoplasia in rodents and humans (Santoni-Rugiu et al, 1996; Michalopoulos and DeFrances, 1997). Sustained myc expression in hepatocytes of transgenic zebrafish and medaka overexpressing myc resulted in hyperplasia and, in zebrafish only, possible hepatocellular adenoma (Gong et al, 2011; Menescal et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish can develop a wide spectrum of tumors in almost every tissue, which greatly resemble human malignancies in both histological characteristics and gene expression profiles [ 7 10 ]. Our previous study revealed that transgenic expression of mouse Myc in zebrafish lead to liver tumors [ 11 ] and another study also reported liver hyperplasia in medaka caused by transgenic expression of a quite divergent medaka myc gene [ 12 ]; however, so far no study has documented the oncogenicity of zebrafish myc . Due to the whole genome duplication occurred during fish evolution following divergence of the teleost and tetrapod lineages, the zebrafish genome contains two myc genes orthologous to human MYC , i.e.…”
Section: Introductionmentioning
confidence: 99%